D-PLEX100 in an Abdominal Surgery Incision Model in Miniature Swine: Safety Study. (July 2020) - Ramot, Yuval; Nedvetzki, Shlomo; Rosenfeld, Sefi; Rousselle, Serge D.; Nyska, Abraham; Emanuel, Noam
Surgical site infections (SSIs) are a common surgical-related complication. To avoid these complications, a new biodegradable polymer–lipid encapsulation matrix that provides controlled release of doxycycline (doxycycline/polymer-lipid encapsulation matrix [D-PLEX]) has been developed. The aim of this comprehensive study was to evaluate the potential safety of D-PLEX100 in abdominal surgical site. D-PLEX100 was administered into incisions of abdominal surgical site in Yucatan miniature swine, which were followed for up to 6 months and compared to sham-control swine. The D-PLEX100 mass did not migrate from the incisional site, and there was no evidence for systemic toxicity or other safety concerns. Surgical incision sites, including the peritoneal surface, were fully healed at 6 months in all animals. Most of the D-PLEX100 mass was absorbed during the first 3 months, and by 6 months, D-PLEX100 was fully absorbed. Toxicokinetic evaluation revealed that doxycycline concentrations were evident at 30 minutes and persisted to 8 days (71 mg/kg) or at least 15 days (284 mg/kg) and were no longer present in plasma by day 29. This study supports the safety of D-PLEX100 and its favorable degradability profile. A clinical study is being performed to assess the safety and the efficacy of D-PLEX100 to prevent human abdominal SSIs.